On one problem of stochastic control - Sverdan, M. L.; Yurchenko, I. V.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove a comparison theorem for solutions of nonlinear stochastic differential equations with Poisson perturbations and delay. We consider one problem of stochastic control.